Haci Bektashi Veli’s Life in the Light of Debates - Salman, Özcan (Journal of Alevism-Bektashism Studies, 2022)
Haci Bektashi Veli’s life has been discussed by many researchers in Turkey for a long time. There have been significant divergences over time in these studies, and different ideas have emerged, up to the question on his belief. This study discusses Haci Bektashi Veli’s first activities in Anatolia, his role in the Babai uprising, and the days he spent in Sulucakaraoyuk, starting from his life before he came to Anatolia. On the other hand, the study also emphasizes his communication with distinguish persons, his contemporaries. The ideas that the researchers put forward over time were discussed based on main sources, considering every stage of Hunkar’s life. In this context, especially the matter of Haci Bektashi Veli’s marriage has produced remarkable results. On the other hand, our study also emphasizes the effects of Yesevi order, which is often discussed when it comes to Haci Bektashi Veli, on him and people around him. Along with recent studies, the influences of the Vefai order, which started to be evaluated as an antithesis to the Yesevi teachings, were also discussed from various aspects, and the comments of the researchers and the information from the main sources were evaluated. Some works attributed to Haci Bektashi Veli, such as Makalat, Fevaid, Şerh-i Besmele, Nesayih-i, were also analysed. Today, Haci Bektashi Veli’s ideas are tried to be explained through these works, even at many conferences. However, there is no exact evidence showing that he wrote these works. This raises doubts about many of Hunkar’s views, which are thought to be his ideas. This is why our study includes a brief evaluation of these works. For the same reason, some of the questions asked by Irène Mélikoff and Ahmet Yaşar Ocak, which have not been raised for a long time, have been brought to light again. Although many papers and books have been written about Haci Bektashi Veli till today, there has been no study discussing his historical life through various views, especially in recent times. Therefore, this study aims to discuss the recent debates around main sources, to provide a gathered data on the life of Haci Bektashi Veli, and to close this gap in literature by revealing some misconceptions.